The implementation of QRIS-based payment gateway system for the development of MSMEs - Sinta Asmita; Adhitya Suryantara (New Applied Studies in Management, Economics & Accounting)
This research was conducted to provide an overview of the benefits felt by MSMEs in the food sector in the form of increased turnover, customers, and assets in implementing QRIS (Quick Response Indonesian Standard) as an alternative digital-based payment media. A qualitative approach with the case study method was used in this research. The object of this research is QRIS itself, then MSME actors operating in the culinary sector are the subjects of this research. The focus of this research lies in MSMEs in the Mandalika SEZ area because this area is now one of the tourist areas that is currently busy with visitors. This research uses data collection methods in the form of structured and in-depth interviews, documentation, and also observation. Interviews were conducted with MSME actors in the area around the Mandalika SEZ. The selection of resource persons is based on businesses that have permanent buildings, have implemented or are currently implementing QRIS, have employees, and are preferably owned by the local community. After the data is collected, the researcher analyzes the data and then presents it so that the research results are obtained, then a conclusion is drawn. The results of this research show that the existence of a QRIS-based digital payment system can provide benefits for MSME players in terms of increasing turnover and customers but has not yet caused an increase in assets.